Ayurvedic Management of Stress Induced Psoriasis (Kitibha Kustha) -A Case Study: Life Sciences-Ayurveda - Khaire, Utkarsha; Joshi, Dnyanesh; Chinthala, Rajkumar; Yadav, Deepak (International Journal of Life Science and Pharma Research, 2023)
Psoriasis is a chronic, inflammatory, and hyperproliferative skin disorder. Psoriasis appears as tiny (1 to 2 cm in diameter) lesions over the upper trunk and proximal extremities. We will contrast Kitibha Kushta with it based on its clinical characteristics. About 2% of people with psoriasis have it their entire lives. Medical sciences have adopted numerous therapeutic approaches, however they come with a variety of negative effects. So in this instance, Kitibha kushtha’s case was successfully treated with Shodhan, Shaman, and Bahirparimarjan chikitsa. In this single-case study, a 49-year-old male patient complained of numerous little red lesions on his chest, belly, and back of his thigh, which have been accompanied by acute itching for the past four years.Shodhan and Shirodhara were used in the patient’s treatment. 90% of the patient’s primary and related problems were resolved, and both during and after the end of therapy, the patient’s quality of life improved. Shirodhara and Chikitsa are administered following Shodhana and Shaman. The patient’s symptoms were satisfactorily relieved.